PENGUJIAN HADIS AHAD SEBAGAI SUMBER HUKUM - Syawqi, Abdul Haq (Islamuna: Jurnal Studi Islam, 2018)
In the discourse of hadith science, hadith ahad is in a unique position. This is said because the hadith ahad seems to be seen as the second source of law after the mutawatir tradition. Therefore, in a position, mutawatir tradition does not need to be tested for its truth. So that the truth is worthy of the hadith ahad. Companions, hadith experts, and fiqh experts have different ways of testing the authenticity of hadith. Some friends test the hadith with the Qur'an and hadith with other traditions that are stronger or famous which are sometimes reinforced by rational arguments in the form of analogies. Unlike some friends, hadith experts add other criteria, namely the testing of hadith with sirah nabawiyah which is valid, reason, senses, and history. Rigorous testing criteria carried out by fiqh experts, such as the testing of ahad traditions with the Koran, famous hadith, charity friends, qiyas jali, 'general al-balwa, and al-ushul al-‘ammah. With the descriptive method, this article seeks to unravel the testing of hadith ahad as a source of law, so that the standard of validity of the hadith can be described and the hadith is worthy of being a source of law.[Dalam diskursus ilmu hadis, hadis ahad berada pada posisi yang unik. Dikatakan demikian karena hadis ahad seakan-akan dipandang sebagai sumber hukum kedua setelah hadis mutawatir. Oleh karena itu, secara posisi, hadis mutawatir tidak perlu diuji lagi kebenarannya. Sehingga yang layak dijuji kebenarannya adalah hadis ahad. Para sahabat, ahli hadis, dan ahli fikih mempunyai cara berbeda dalam pengujian otensitas hadis. Sebagian sahabat menguji hadis dengan Alquran dan hadis dengan hadis lain yang lebih kuat atau masyhur yang terkadang diperkuat dengan argumen rasional dalam bentuk analogi. Berbeda dengan sebagian sahabat, ahli hadis menambahkan kriteria lain, yaitu pengujian hadis dengan sirah nabawiyah yang sahih, akal, indra, dan sejarah. Kriteria pengujian yang ketat dilakukan oleh ahli fikih, seperti pengujian hadis ahad dengan Alquran, hadis masyhur, amal sahabat, qiyas jali, 'umum al-balwa, dan al-ushul al-‘ammah. Dengan metode deskriptif, artikel ini berusaha mengurai pengujian hadis ahad sebagai sumber hukum, sehingga standar kesahihan hadis dapat dideskripsikan dan hadis layak dijadikan sebagai sumber hukum]